Associação da Dopplervelocimetria das artérias uterinas com a evolução clínica da Mola hidatiforme - Asmar, Flavia Tarabini Castellani [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Doppler ultrasonography can be used to assess neoangiogenesis, a characteristic feature of postmolar gestational trophoblastic neoplasia (GTN). However, there is limited information on whether uterine artery Doppler flow velocimetry (DFV) can predict GTN following complete hydatidiform mole (CHM). The purpose of this study was: 1) to compare uterine blood flow before and after CHM evacuation between women who developed post-molar GTN and those who achieved spontaneous remission; 2) to assess the usefulness of uterine DFV parameters as predictors of post-CHM GTN, and to determine the best parameters and cutoff values for predicting post-CHM GTN. Methods. This prospective cohort study included246 CHM patients attending three trophoblastic diseases centers (Botucatu -Sao Paulo State University, Rio de Janeiro Federal University and Fluminense Federal University) between 2013 and 2014. Pulsatility index (PI), resistivity index (RI), and sistolic/dyastolic ratio (S/D) were measured by DVF before and 4-6 weeks post CHM evacuation. Statistical analysis was performed using Wilcoxon's test, logistic regression and ROC analysis. Results. No differences in pre- and postevacuation DVF measurements were observed in patients who developed post-CHM GTN. In those that achieved spontaneous remission, PI and SD were increased after evacuation. Pre- and post-evacuation PI was significantly lower in patients who developed GTN with estimates of odds ratio of 13.9-30.5. Pre-evacuation PI ≤1.38 (77% sensitivity, 82% specificity), and post-evacuation PI≤1.77 (79% sensitivity, 86% specificity) were significantly predictive of GTN. Conclusions. Uterine DFV measurements, particularly pre- and post-molar evacuation PI, can be useful for predicting post-CHM GTN
Use of uterine artery Doppler flow velocimetry for the Prediction of gestational trophoblastic neoplasia after complete hydatidiform mole
Keywords: Dopplervelocimetria; Mola hidatiforme; Doença trofoblástica gestacional; Gestational trophoblastic disease